Morphological Features and In Vitro Cytopathic Effect of Acanthamoeba griffini Trophozoites Isolated from a Clinical Case - Arturo González-Robles; Lizbeth Salazar-Villatoro; Maritza Omaña-Molina; Maria Reyes-Batlle; Carmen M. Martín-Navarro; Jacob Lorenzo-Morales (Journal of Parasitology Research)
Light and transmission electron microscopy observations are reported on the structure and in vitro cytopathic effect of Acanthamoeba griffini trophozoites isolated from a clinical case. Live trophozoites were moderately active with a remarkable pleomorphism which changed from ovoid to quite elongated shapes. When moving, amoebae formed cytoplasmic projections such as wide lamellae and acanthopodia of diverse size and thickness which contain a significant amount of actin. Ultrastructurally, the cytoplasm showed the main organelles found in other free-living amoebae. Coincubation of trophozoites with MDCK cell monolayers resulted in a local damage to target cells after 24 h of interaction, suggesting that the cytopathic effect is contact-dependent. By transmission electron microscopy, amoebae appeared to engulf small portions of the MDCK cells; however, the cells that were not in contact with trophozoites had an unaltered morphology. When epithelial monolayers were incubated with conditioned medium for 24 h, small areas of cell injury were also observed. The phylogenetical analysis as well as the sequencing of the acquired amplified product for the DF3 region of the amoebae isolate confirmed that it belongs to genotype T3, which includes other pathogenic amoebae; besides the activity of two drugs currently used against Acanthamoeba was tested on A. griffini.